Take home messages with cases from focused update on echocardiographic assessment of aortic stenosis. Issue 16 (23rd March 2018) - Hung, Judy; Klassen, Sheila Liu; Bermejo, Javier; Chambers, John Boyd
Abstract : Echocardiography plays an important role in the assessment of valvular aortic stenosis. Updated recommendations focusing on a stepwise approach to evaluating aortic stenosis have recently been published by the European Association of Cardiovascular Imaging and the American Society of Echocardiography. This review uses illustrative cases to demonstrate technical aspects of aortic stenosis assessment and use of the new proposed classification scheme for aortic stenosis. Key points from the updated recommendations reviewed in this paper are: (1) technical considerations and sources of error in measurement of peak velocity, mean aortic valve gradient and aortic valve area by continuity equation. (2) Application of flow status using indexed left ventricular stroke volume to distinguish patients with low gradients and a low calculated aortic valve area. (3) Use of low-dose dobutamine stress echocardiography in patients with low ejection fraction. (4) Application of the new classification scheme and review of algorithm use for echocardiographic evaluation of severe aortic stenosis. Improved understanding of how to handle unmatched variables and adopting an integrated approach to determine severity is central to guiding the clinician's management of aortic stenosis.